Sliding Mode Controller-Based BFCL for Fault Ride-Through Performance Enhancement of DFIG-Based Wind Turbines. (15th May 2020) - Firouzi, Mehdi; Nasiri, Mojtaba; Mobayen, Saleh; Gharehpetian, G. B.
Abstract : The fault ride-through (FRT) capability and fault current issues are the main challenges in doubly fed induction generator- (DFIG-) based wind turbines (WTs). Application of the bridge-type fault current limiter (BFCL) was recognized as a promising solution to cope with these challenges. This paper proposes a nonlinear sliding mode controller (SMC) for the BFCL to enhance the FRT performance of the DFIG-based WT. This controller has robust performance in unpredicted voltage sag level and nonlinear features. Theoretical discussions, power circuit, and nonlinear control consideration of the SMC-based BFCL are conducted, and then, its performance is verified through time-domain simulations in the PSCAD/EMTDC environment. To reduce the chattering phenomenon and decrease the reaching time, it used the exponential reaching law (ERL) for designed SMC. Also, the SMC-based BFCL performance is compared with the conventional and PI controller-based BFCL for both symmetrical and asymmetrical short-circuit faults. Simulation results reveal that the SMC-based BFCL provides better performance compared with the conventional and PI controller-based BFCL to enhance the FRT.